Virtual Reality Effectivity to Increase Self-Efficacy in Suction Skill among Nursing Student: Quasi Experiment Study - Ashamar Puri Apsari; Restuning Widiasih; Ristina Mirwanti (Universitas Padjadjaran, 2023)
Virtual reality is a technology-based learning media designed to increase student self-efficacy in performing nursing skills, one of which is suctioning. However, virtual reality has yet to be tested for its effectiveness. This study aims to determine virtual reality learning media's effectiveness in increasing student self-efficacy in performing suction nursing actions. This study used a quasi-experiment method with a one-group pre-test post-test design approach. The population in this study were 191 active students of the Faculty of Nursing, Universitas Padjadjaran. The sampling technique used was purposive sampling and obtained a sample of 68 people by the inclusion and exclusion criteria. The instrument used was a self-efficacy questionnaire developed from Bandura's theory and consisted of 35 statement items. Selected respondents filled out the pre-test and were then given an intervention by performing suction nursing actions using virtual reality after completing the post-test. Data were analyzed using the non-parametric Wilcoxon signed rank test because the data were not normally distributed. After being given the intervention, there was an increase in student self-efficacy in performing suction nursing actions, as evidenced by an increase in the median in the post-test results (113.5) compared to the pre-test results (102). The test results on the Wilcoxon signed rank test showed that the p-value showed a significant difference in self-efficacy after using virtual reality learning media (p = 0.00). Virtual reality learning media can increase student self-efficacy in performing suction nursing actions.